Development of Institutions, Participation and Independence of Farmers' Groups in Supporting the Palm Cattle Integration Program in Paser Belengkong - Suherman, Edi; Maulana, Delly; Bida, Obed (Pancasila International Journal of Applied Social Science, 2024)
The objectives of the study are: (1) strategies in improving management and changing mindset (2) analyzing the influence of farmer groups that are still unstructured. (3) analyze efforts in fostering independence and participation. (4) analyze the steps in creating social relationships as well as intense communication. The research method used is quantitative method with data collection instruments. The results of the study are: (1) Strategies in improving management and changing mindsets have a significant influence (2) Unstructured institutions can have a negative influence (3) Independence and participation of members can have a negative influence (4) Social relationships and intense communication can have a significant influence on the development of farmer groups. Conclusion: (1) A mindset that has not been well managed will have a negative influence (2) Various efforts need to be made in developing farmer group institutions (3) the ability of farmer groups to make decisions (4) Social relations and communication that are not harmonious and intense can have a negative influence on farmer groups.